PENGARUH TINGKAT PROFESIONALISME DAN KEPRIBADIAN TERHADAP KUALITAS GURU SMK UNGGUL SAKTI KOTA JAMBI - Pratiwi Indah Sari (Universitas Batanghari Jambi, 2017)
The purpose of this research is to find : Influence of professionalism and personality toward quality of teacher accordance with simultanously in SMK Unggul Sakti Jambi town. From the simultaously statistical variable, the result from the two test of independent variable were influentally the quality of teacher has proven to be is the personality had the dominant influentally toward quality of teacher in SMK Unggul Sakti Jambi town. At last, the character has to be firm is the personality were the biggest variable for the quality of teacher determine in SMK Unggul Sakti Jambi town.Keyword: Professionalism, Personality, Quality, Teacher, Student.